Integrating grey sequencing with the genetic algorithm–immune algorithm to optimise touch panel cover glass polishing process parameter design. Issue 16 (17th August 2016) - Wang, Shen-Tsu
Abstract : The touch panel cover glass is one of the important parts and components that determine touch panel quality. The quality requirement of touch panel cover glass emphasises the stability of glass thickness. As this factor directly influences the induction effect and touch of the touch panel, the parameter conditions for the cover glass polishing process have significant impact. This study integrated grey sequencing with the Genetic algorithm–Immune algorithm to optimise the parameter design for the touch panel cover glass polishing process. The experimental measurement value was the thickness value of the processed glass, and the uniformity of glass thickness after processing was discussed. The optimum processing combination influencing the process conditions is as follows: the ambient temperature is 22 (°C), the processing pressure is 0.04 (Mpa), the processing time is 30 (min), the machine speed is 70 (rpm), the polishing solution concentration is 1.4 (g/cm 3 ), the central particle size of polishing powder is 1.4 (um) and the process capability C pk is 1.75, which is better than the process capability of C pk 1.41 of the response surface methodology and the process capability of C pk 1.37 of the Taguchi experimental design.